2002
DOI: 10.1002/1521-3773(20020215)41:4<597::aid-anie597>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Akashins A, B, and C: Novel Chlorinated Indigoglycosides fromStreptomyces sp. GW 48/1497

Abstract: Sky blue akashins (see picture) are the first indigoglycosides and the first natural derivatives of 5,5′‐dichloroindigo to be isolated from terrestrial Streptomyces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…The marine-derived actinomycete strain F001 is known to produce two compound classes of biomedical interest, the chlorinated indigo glycoside akashin A (1) and several congeners of the diazaquinomycin class of antibiotics (2). Akashin A has demonstrated cytotoxic activity against cancer cell lines (3), whereas it was recently reported that some diazaquinomycin analogs exhibited potent and selective inhibitory activity against a panel of drug-resistant Mycobacterium tuberculosis strains (4).…”
Section: Announcementmentioning
confidence: 99%
“…The marine-derived actinomycete strain F001 is known to produce two compound classes of biomedical interest, the chlorinated indigo glycoside akashin A (1) and several congeners of the diazaquinomycin class of antibiotics (2). Akashin A has demonstrated cytotoxic activity against cancer cell lines (3), whereas it was recently reported that some diazaquinomycin analogs exhibited potent and selective inhibitory activity against a panel of drug-resistant Mycobacterium tuberculosis strains (4).…”
Section: Announcementmentioning
confidence: 99%
“…On this account are interesting the indigo N-glycosides (blue sugars) 3 , the analogues of naturally occuring akashins 4 showing considerable effect against various human cancer cells. Among other N-glycosidic indole derivatives with promising cancerostatic effects belong staurosporine, K-252d, rebeccamycine and tjipanazoles.…”
Section: Somementioning
confidence: 99%
“…Some N-glycosides show antineoplastic effects [24]. The indigo N-glycosides (blue sugar), the analogues of naturally occurring akashins [25] showed considerable effect against various human cancer cell. As a review article [26] summarizes the synthesis, structure and evaluation of biological activities of the N-glycosides containing quinazoline skeleton has been published.…”
Section: Introductionmentioning
confidence: 99%